AB0117 Saliva in patients with different rheumatic diseases. (1st June 2001) - Helenius, M; Meurman, JH; Helenius, I; Kari, K; Hietanen, J; Suuronen, R; Kautiainen, H; Leirisalo-Repo, M; Lindqvist, C
Abstract : Background: Rheumatic diseases affect salivary glands. 1 However, data is sparse on saliva of patients with different disease subgroups with expected differencies. Objectives: We studied salivary flow and biochemistry in 22 patients with spondyloarthropathy (SPA), 19 with ankylosing spondylitis (AS), 25 with rheumatic arthritis (RA) and 19 with mixed connective tissue disease (MCTD) and 85 age- and sex- matched controls. The mean age was 44.5 years and duration of disease 10.5 years. Methods: Minor salivary gland biopsies were taken for inflammatory focus score, and salivary components analysed biochemically. 2 Results: The results showed an inverse correlation between focus scores and decreased salivary flow rates (R = -0.48, CI 0.64–0.29 for resting flow, R = -0.49, CI 0.65–0.30 for stimulated flow). Compared with controls, decreased resting flow (<0.1 mL/min) was most frequent in AS group (22% vs. 0%, p < 0.05), while decreased stimulated flow (<0.7 mL/min) was most frequent in the MCTD group (60% vs.16%, p < 0.05). Lower concentrations of salivary amylase (p < 0.001), but higher albumin (p < 0.01), total protein (p < 0.001), IgA (p < 0.05), IgG (p < 0.001) and IgM (p < 0.001) were found in the patients. Conclusion: Thus, the hypothesis was confirmed showing significant differences in salivary parameters between patients and controls, and also differences between the patients with various rheumatic diseases. References: Daniels. Scand J Rheum. 1986;61:36–43 Pajukoski, et al . Oral Surg. 1997;84:265–71